ACCOMMODATION INFRASTRUCTURE AND TOURISM FLOWS ON FELEACU HILL (CLUJ COUNTY) - Daniela-Livia GHEORGHIEȘ (Studia Universitatis Babeş-Bolyai: Geographia, 2016)
Accommodation Infrastructure and Tourism Flows on Feleacu Hill (Cluj County). Feleacu Hill experienced tourism development between 2001 and 2015. The INS data indicates that the number of accommodation units increased from one (2001) to four (2015) and there are a few more which are not registered in the INS database. The accommodation capacity increases, as many guesthouses are expanding their premises to receive more tourists and new accommodation units emerge, such as Hotel Premier in Vâlcele (Feleacu commune). Tourism flows also registered a highly positive trend. The number of arrivals increased from 95 tourists in 2002 to 7791 tourists in 2015. However, there was a downturn between 2009 and 2012, due to the economic crisis and the opening of the Turda – Gilău motorway (A3), which redirected transit routes outside the region and led to the closure of Paradis Hotel in 2012. Since 2012, the number of arrivals and overnight stays increased steadily due to the development of new forms of tourism – rural tourism, agrotourism, extreme tourism and complex tourism, materialized in growing numbers of tourists at the two guesthouses in Ciurila commune (“La Mesteceni” and “Domeniul Regilor”). Tourism brings obvious benefits to the rural communities on Feleacu Hill, even if the average duration of stay is still low.